TBIO-20. CLINICAL TUMOR WHOLE EXOME SEQUENCING FOR PEDIATRIC NEURO-ONCOLOGY PATIENTS – RESULTS FROM THE BAYLOR ADVANCING SEQUENCING IN CHILDHOOD CANCER CARE (BASIC3) CLINICAL SEQUENCING STUDY. Issue 2 (22nd June 2018) - Lin, Frank; Potter, Samara; Ting, Michelle; Chandramohan, Raghu; Kakkar, Nipun; Wang, Tao; Raesz-Martinez, Robin; Scollon, Sarah; Bergstrom, Katie; Lopez-Terrada, Dolores; Adesina, Adekunle; Mohila, Carrie; et al.
Abstract: Tumor mutations detected by genomic tests such as whole-exome sequencing (WES) have the potential to affect clinical management; however, data regarding clinical utility in pediatric neuro-oncology are limited. In order to investigate this topic, enrollment onto the BASIC3 clinical exome sequencing study was offered to children with newly-diagnosed CNS and non-CNS solid tumors. WES was performed on tumor (when available) and blood specimens in a certified clinical laboratory, with resulting genetic variants categorized by perceived clinical relevance and reported to the electronic health record. Mutations were also annotated following recent consensus guidelines (Li et al. J Mol Diagn 2017). WES was performed on 71 tumors obtained from 70 of 98 patients with CNS tumors on the BASIC3 study (71%), including embryonal tumors (medulloblastoma, n=18; PNET or pineoblastoma, n=5), LGG (n=9), HGG (n=7), and ependymal tumors (n=9). Analysis per the new guidelines revealed 21% (15/71) of tumors harbored a variant of "Strong Clinical Significance" (Tier 1) and 27% (19/71) a variant of "Potential Clinical Significance" (Tier 2). Targetable mutations involved the MAPK pathway (BRAF x 6, KRAS, FGFR1), PI3K/MTOR pathway (TSC1, PIK3CA), SWI/SNF family (SMARCB1, SMARCA4), and other protein kinases (PDGFRA x 2). The rate of clinically relevant mutations differed by histology, with frequent variants in LGG (4/9, 44%), HGG (6/7, 86%), and medulloblastoma (7/18, 39%), but not ependymal tumors (0/9, 0%). These data highlight the promise of clinical genomic testing for pediatric brain tumor patients as well as the need for integrated (DNA/RNA) genomic tumor testing to maximize diagnostic yield.